Prolonged mask wearing changed nasal microbial characterization of young adults during the COVID-19 pandemic in Shanghai, China - Xiang, Guoxiu; Xu, Kai; Jian, Ying; He, Lei; Shen, Zhen; Li, Min; Liu, Qian (Frontiers in Immunology, 2023)
Background Face masks have become a common sight during the Coronavirus Disease 2019 (COVID-19) pandemic in many countries. However, the impact of prolonged face mask wearing on nasal microbiota of healthy people is not fully understood. Methods In this study, we compared the nasal microbiota of 82 young adults who wore face masks for an extended period of time to 172 mask-free peers from the same school recruited before the COVID-19 pandemic via 16S ribosomal RNA gene sequencing. Diversity, composition, and function of nasal microbiota between the two groups were analyzed. Prevalence of commensal bacteria colonized in the nasal cavity was determined by culture-based analysis. Results We observed that prolonged face mask wearers had significantly different nasal microbial characterization and metabolic function compared to mask-free controls from 2018. Specifically, the nasal microbiota of the prolonged mask wearers displayed increased abundance of Staphylococcus, Pseudoalteromonas, Corynebacterium, etc. Meanwhile, the abundance of several genera including Bacteroides, Faecalibacterium, and Agathobacter was decreased. Moreover, we observed that COVID-19 infection history did not affect the composition of nasal microbiota significantly. Additionally, the culture-based analysis revealed that Staphylococcus aureus and Corynebacterium accolens increased, and Staphylococcus epidermidis decreased in the nasal cavity of prolonged mask wearers. Conclusions Overall, our study suggests that prolonged face mask wearing can significantly alter the nasal microbiota.